Peran Kepemimpinan Transformasional dan Kecerdasan Emosional dalam Meningkatkan Kinerja Karyawan (Studi pada Proyek Konversi Energi Batubara PT X di Gresik) - Noermijati, Noermijati; S, Catarina Dyan (Universitas Brawijaya, Indonesia, 2011)
This study aims to analyze the influence of transformational leadership and emotional intelligence on the performance of employees, the studies at Coal Energy Conversion Project PTX in Gresik. To achieve these objectives the research was conducted the method of explanatory that is explain the causal relationship between variables transformational leadership and emotional intelligence and its influence on employee performance. The population in this study were 63 employees. While the sampling technique was done by total sampling so that the entire population in this study is the research sample. The techniques of data analysis in the study was conducted using multiple linear regression. The results showed that simultaneously transformational leadership and emotional intelligence significantly influence to the performance of employees. the first hypothesis was acceptable which stated that simultaneously, there was a significant influence between the two variables, transformational leadership and emotional intelligence, Partially there was the influence of transformational leadership on employee performance. Moreover, the emotional intelligence had a significant influence on the performance of employees. Independent variables that had a dominant influence on performance was transformational leadership thus it proved that the third hypothesis in this study was also acceptable.